Colonial Cities in Motion Urban Symbolism and Popular Radicalism - Abidin Kusno (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
This paper concems with the change in the visual environment of colonial city and the ways in which they helped to shape political imagination. What kinds of architectural and urban spectacles were constructed and what role did they play in contributing to the formation of alternative identities for the Indonesians under Dutch colonial rule? How could colonial cities be understood less as a "form of dominance", but rather a city that was appropriated by the colonized to produce unintended consequences that contributed to the undermining of colonial power? The focus of this paper is thus the political implications of the visual environment of the colonial city. I rely on literature and a range of discursve visual representations in documenting the ways in which the material city was experienced in its wider social political context. Yet what can we except from the visual environment?